발반사 마사지가 유방암 환자의 수술 후 통증과 수면만족도에 미치는 효과 - 이홍숙 (The Graduate School, Ajou University, 2005)
This study, a quasi-experimental study using a nonequivalent control group pretest-posttest design, conducted a survey on 30 patients test group and control group of 15 patients sampling an adjacent population at random - who are operated on the breast cancer and are in the A University Hospital located in Suwon, to examine into the effects of foot reflex zone massage on their pain and sleep satisfaction through the nursing interventions. It gave them a foot reflex zone massage for the total 30 minutes - basic massage 10 minutes and reflex massage 20 minutes required to alleviate their pain day in day out covering a two-month period from the first of July to the first of September 2004, for the purpose of collecting data. It launched into a two-round foot reflex zone massage at 6 and 24 hours since mastectomy through a direct visit at the hospital room to measure pain intensity, physiological index (pulse and blood pressure) and sleep satisfaction of them. The results are as follows. First, it showed that there is all the difference between pain intensity of test group and that of control group. In result, the first hypothesis, 　pain of test group, which measure at 6 (p= .000) and 24 hours (p= .001) since mastectomies, will be bigger than that of control group　, was established. Second, it showed that there is all the difference between physiological index of test group and that of control group. In result, the second hypothesis, 　pulse (p= .025, p= .002), systolic blood pressure (p= .004, p= .012) and diastolic blood pressure (p= .004, p= .003) of test group, which investigate at 6 and 24 hours since mastectomies, will be bigger than that of control group　, was established. Third, it showed that there is no significant difference between two groups in the frequency using an analgesic during 24 hours since the first massage (p= .068); test group and control group is an average .8 times and .4 times, respectively. In result, the third hypothesis, 　test group will make a little use of an analgesic compared to control group　, was not established. Fourth, it showed that there is a significant difference between sleep satisfaction of test group and that of control group (p= .000). In result, the fourth hypothesis, 　sleep satisfaction of test group, which examine in the morning after mastectomies, will be bigger than that of control group　, was established. In the result, a foot reflex zone massage is seen to be effective in the pain reduction and sleep promotion of patients who are operated on breast cancer, and in providing them with more qualitative care by improving confidence between them and nurses through a physical touch. Also, it can be applied to a clinical examination through an independent nursing intervention.
학위논문(석사)--아주대학교 대학원 :간호학과,2005